Randomized controlled trial to evaluate the effects of progressive resistance training compared to progressive muscle relaxation in breast cancer patients undergoing adjuvant radiotherapy: the BEST study - Potthoff, Karin; Schmidt, Martina; Wiskemann, Joachim; Hof, Holger; Klassen, Oliver; Habermann, Nina; Beckhove, Philipp; Debus, Jürgen; Ulrich, Cornelia; Steindorf, Karen (BMC cancer, 2013)
Cancer-related fatigue (CRF) is one of the most common and distressing side effects of cancer and its treatment. During and after radiotherapy breast cancer patients often suffer from CRF which frequently impairs quality of life (QoL). Despite the high prevalence of CRF in breast cancer patients and the severe impact on the physical and emotional well-being, effective treatment methods are scarce.